Frequency of Caesarean Section in patients undergoing trial of Labor after Caesarean Section (TOLAC) - Neha Farooq, Sadia Habib, Sidra Dilpazeer, Nimra Naeem, Salma Rehman, Sundus Nawaz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To estimate the rate of C-section in patients undergoing TOLAC (trial of labour after cesarean section). Study design: Descriptive case series. Place and duration of study: Department of Obstetrics & Gynecology Ward, Ayub Teaching Hospital Abbottabad from 1st October 2020 to 1st April 2021. Methodology: One hundred and fifty-seven pregnant women with previous one caesarean section were included in the study. Basic demographics like age, gestational age, parity and weight were recorded. Results: The mean age was 28.09±5.37 years, mean gestational age was 37.79±2.36 weeks, mean weight 68.66±5.49 Kg, mean height 1.65±0.04 meters, mean BMI 25.11±2.77 Kg/m2 and mean estimated fetal weight was 2.95±0.55 kg. Caesarean section was observed in 84.1% patients. Conclusion: Unsuccessful TOLAC was higher in women admitted with history of previous caesarean section. Keywords: Caesarean section, Trial of labor after caesarean section, Unsuccessful